Economic efficiency of management decisions - Han, Pengbo; Tu, Jinguo; Maslak, M. V. (Національний технічний університет "Харківський політехнічний інститут", 2024)
Cost-effectiveness of management decisions is critical to ensuring the success of a business and achieving its goals. It supports the sustainable development of the company, ensures competitiveness in the market and contributes to increasing the value of the enterprise for stakeholders.
Економічна ефективність управлінських рішень
Keywords: economic efficiency; business; management decisions; market; competitiveness